دور رسالة المنظَّمة في بناء الميزة التَّنافسيَّة (دراسة مسحيّة في شركتي الاتصالات الخلويَّة السُّوريَّة في محافظة اللاذقيَّة) - سليطين سوما; محمد ليلان (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت هذه الدّراسة للتَّعرف على العلاقة بين رسالة المنظَّمة والميزة التَّنافسية في شركتي الاتصالات الخلويَّة السُّوريَّة في محافظة اللاذقيَّة، من خلال تحديد دور رسالة المنظَّمة في تحقيق ثلاثة من أبعاد الميزة التَّنافسيَّة: الجودة المتفوّقة، التَّطوير المتفوّق، الاستجابة المتفوّقة لحاجات ورغبات العملاء، وقد اعتمد الباحث على كل من المقاربة الاستنباطيَّة كمنهج عام للبحث، والمنهج الوصفي، وقام بتوزيع استبانة على كافة مديري شركتي الاتصالات الخلويَّة السُّوريَّة في محافظة اللاذقيّة، كما قام بمقابلة معظمهم خلال هذه الدّراسة. وقد خلصت الدّراسة إلى وجود علاقة طرديّة معنويّة بين رسالة المنظَّمة وبناء الميزة التَّنافسيَّة. وكانت النّتيجة الرّئيسة التي توصّل اليها الباحث هي امتلاك الشّركات محل البحث لرسالة واضحة ومفهومة لها دور كبير في بناء ميزتها التَّنافسيّة. أمَّا أهم التّوصيات فكانت: العمل على إظهار القوى الدّافعة والموارد المتميّزة في رسالة كل شركة من الشّركات محل البحث، والاهتمام بموردهم البشري، وعملائهم. الأمر الَّذي يسهم في تعزيز الميزة التَّنافسيَّة لدى الشّركات محل البحث مستقبلاً. This study aimed at identifying the relationship between the Organization’s Mission and Competitive Advantage in the two Syrian cellular communications in Lattakia province. By Identifying the Role of organization’s mission in achieving three dimensions of competitive advantage: Superior Quality, Superior Development, Superior Customers Responsiveness. The researcher relied on Both, the Deductive Approach as a general method, and the Descriptive Approach, and he gave a questionnaire to all company Syrian cellular communications managers in Lattakia, and has also interviewed most of them during this study. The Study Showed that there is a Significant Positive Relationship between the organization’s mission and build competitive advantage. The researcher has provided a summary of the main result that have found out is, that possession of companies under study of clear and understandable mission, that has a big role in building its competitive advantage. The main recommendations were: Work to show the driving forces and resources in the mission of each company of the companies under study, and focus on the human resource, and their customers . Which contributes to strengthening the Competitive Advantage of the companies under study in the future.